PENGARUH DEBT TO EQUITY RATIO (DER) DAN RETURN ON EQUITY (ROE) TERHADAP EARNING PER SHARE (EPS) PADA PT. AGUNG PODOMORO LAND TBK PERIODE 2013-2022: Ilham Febriansyah - Ilham Febriansyah (Samudra Publisher, 2024)
This research aims to determine the effect of Debt to Equity Ratio and Return on Equity on Earning Per Share at PT. Agung Podomoro Land Tbk for the 2013-2022 period, both partially and simultaneously. The research method used in this research is quantitative research. The data analysis used in this research is the classical assumption test, multiple linear regression test, correlation coefficient analysis, coefficient of determination analysis, t test and F test. The results of this research are that the Debt to Equity Ratio and Return on Equity have a significant effect on Earning Per Share with the regression equation Y = 7873.440 + 0.003X1 + 0.003X2. The correlation coefficient value is 0.921, meaning it has a very strong relationship. The coefficient of determination value is 84.4% while the remaining 15.6% is influenced by other factors. Hypothesis testing obtained a value of Fcount > Ftable (19.550 > 4.459) that the variables Debt to Equity Ratio (X1) and Return on Equity (X2) have a significant effect on Earning Per Share (Y) at PT. Agung Podomoro Land Tbk for the 2013-2022 period. Based on the determination test, it can be concluded that the Debt to Equity Ratio and Return on Equity have an effect of 84.4% on Earning Per Share. Meanwhile, the remaining 15.6% was influenced by other variables not examined in this research.